Development of a hospital deprescribing implementation framework: A focus group study with geriatricians and pharmacists. (11th November 2019) - Scott, Sion; Twigg, Michael J; Clark, Allan; Farrow, Carol; May, Helen; Patel, Martyn; Taylor, Johanna; Wright, David J; Bhattacharya, Debi
Abstract: Background: over 50% of older people in hospital are prescribed a pre-admission medicine that is potentially inappropriate; however, deprescribing by geriatricians and pharmacists is limited. This study aimed to characterise geriatricians' and pharmacists' barriers and enablers to deprescribing in hospital. It also intended to develop a framework of intervention components to facilitate implementation of hospital deprescribing. Methods: fifty-four geriatricians and pharmacists representing four UK hospitals attended eight focus groups. We designed a topic guide to invite discussions about barriers and enablers to deprescribing. After thematic analysis, themes were mapped to the theoretical domains framework (TDF), enabling prioritisation of domains for behaviour change. We then identified evidence-based intervention components for changing behaviour within prioritised TDF domains. Results: geriatricians and pharmacists described several deprescribing enablers in the hospital setting including alignment with their role and generalist knowledge, and routine patient monitoring. Five prioritised TDF domains represent the key barriers and enabler: patient and caregiver attachment to medication (social influence); perceptions that deprescribing is riskier than continuing to prescribe (beliefs about consequences); pharmacists' working patterns limiting capacity to support deprescribing (environmental context and resources); deprescribing being a low hospital priority (goals) and incentives to deprescribe (reinforcement). Prioritised TDF domains aligned with 44 evidence-based intervention components to address the barriers and enabler to hospital deprescribing. Conclusion: the behavioural determinants and their associated intervention components provide a hospital deprescribing implementation framework (hDIF). Intervention components should be selected from the hDIF to provide a theory and evidence-based intervention tailored to hospital contexts.